Downregulation of IRF7-mediated type-I interferon response by LmCen –/– parasites is necessary for protective immunity - Telly Sepahpour; Jalal Alshaweesh; Nazli Azodi; Komudi Singh; Derek D. C. Ireland; Farzaneh Valanezhad; Risa Nakamura; Abhay R. Satoskar; Ranadhir Dey; Shinjiro Hamano; Hira L. Nakhasi; Sreenivas Gannavaram (npj Vaccines)
Abstract Leishmaniasis is a tropical disease caused by Leishmania parasites and currently has no licensed vaccines. We developed a dermotropic Leishmania major centrin gene-deleted strain (LmCen –/–) as a live attenuated vaccine. Recent studies have shown that type I interferons (IFNs) play important roles in immunity to parasitic and viral pathogens. However, their relevance in protective immunity following vaccination is not understood. We found that immunization with LmCen –/– induces a transient increase in type I IFN response along with its regulatory factor IRF7 that is downregulated 7–21 days post-immunization, coincided with the induction of a robust Th1 adaptive immune response. Challenge infection with virulent L. donovani parasites showed a significant reduction of splenic and hepatic parasite burden in IRF7–/– mice than wild type mice following immunization with LmCen –/– , suggesting that ablation of type I IFN response is a pre-requisite for the induction of LmCen –/– mediated Th1 immunity against L. donovani infection.